2018
DOI: 10.4088/jcp.17m11599
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Free Status in Community-Dwelling Patients With Schizophrenia in China

Abstract: Antipsychotic-free status was more common in community-dwelling patients with schizophrenia in the rural area than in the urban area. Older age and poorer attitude toward medication treatment were common features of antipsychotic-free patients. There were correspondingly different risk factors for antipsychotic-free status between rural and urban areas. Building a positive medication treatment attitude is an important strategy for establishing medication adherence in older, community-dwelling patients with sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…For patients that did not attend medical homes, rural patients had a higher number of monthly specialty mental health visits, higher medication adherence, and less inpatient hospitalizations than urban patients (Kilany et al, 2018). In a large study in China, with 1,365 participants, Hou et al (2018) compared rural and urban community dwelling patients with regards to antipsychotic-free status. The proportion of antipsychotic-free patients was significantly higher in the rural area than in the urban area (35.4% vs 17.5%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients that did not attend medical homes, rural patients had a higher number of monthly specialty mental health visits, higher medication adherence, and less inpatient hospitalizations than urban patients (Kilany et al, 2018). In a large study in China, with 1,365 participants, Hou et al (2018) compared rural and urban community dwelling patients with regards to antipsychotic-free status. The proportion of antipsychotic-free patients was significantly higher in the rural area than in the urban area (35.4% vs 17.5%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This finding does not necessarily mean that prognosis of schizophrenia is worse in rural areas; rather, it may be better perceived as the result of inadequate access to services and treatments by patients in rural areas. Moreover, the proportion of patients that did not receive antipsychotic treatment was higher in rural areas than in urban areas in China (Hou et al, 2018; Wei et al, 2020). It seems that the lack of mental health resources in rural areas may account for these treatment shortages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urban population received food from state grain stores, showing how urbanicity can affect resource access [31]. Another Chinese study showed that patients in rural compared to urban areas were less likely to take antipsychotics (35.4 vs. 17.5%) [32]. Lower education, living alone and number of admissions were predictors of not taking antipsychotics in urban areas, whereas female sex, low BMI, higher positive symptoms, lower anxiety and insight emerged as predictors in rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…This review shows that urban environments do not increase the risk for psychosis by default, but that their effects are conditional on multiple factors. For instance, city living can offer benefits, like access to healthcare or resources, especially in less developed countries [31,32]. However, it is also characterized by lack of green space and high-intensity social encounters that might be particularly stressful for individuals with an increased liability for psychosis [36 ▪▪ ,39].…”
Section: Discussionmentioning
confidence: 99%